(untitled) (Research, Society and Development, 2020)
The strawberry fruit is very sensitive and easily damaged, generating large post-harvest losses, both commercial and nutritional. Therefore, the improvement of new storage technologies is needed to reduce the both nutrients and sensors losses, increase profitability and maintain it as the organoleptic features of the product. The present work aims to evaluate the chemical characteristics of organic strawberry fruits, whole and processed, conditioned in different packages under freezing for 105 days. Four procedures were used (Pulp with clear plastic packaging; Pulp with plastic-wrapped aluminum; Whole lid with transparent plastic; Whole lid with plastic-wrapped aluminum) for 105 days. The fruits were analyzed for soluble solids, titratable acidity, phenolic compounds, SS / TA ratio, and ascorbic acid. Titratable acidity shows a reduction from 21 days of storage for whole fruits and from 42 days when shipped on aluminum foil. The soluble solids content also decreases due to storage, being more pronounced in whole fruits wrapped in aluminum. Ascorbic acid shows a decrease in all treatments after freezing but remains stable throughout the storage period. The SS / TA ratio decreased with freezing pulp but remained stable until the last evaluation. Phenolic compounds increase over the freezing period of both pulp and fruit, with or without aluminum foil as a wrapper in the package. In general, or frozen, it is suitable for maintaining the chemical properties of strawberry fruits. A pulp as storage was more effective in maintaining the chemical properties of the fruit. For most of the characteristics analyzed, aluminum foil does not contribute significantly to the maintenance or improvement of pulp/fruit chemical properties when frozen.